Maternal–Neonatal Methylome Signatures In Preterm Birth Revealed By Long-Read DNA Methylation Profiling - BalaSubramani Gattu Linga (19325617) (2025)
Background Preterm birth (PTB) remains a leading cause of neonatal morbidity and mortality, driven by complex maternal–fetal biological interactions. Epigenetic regulation, particularly DNA methylation, is increasingly recognized as a key mediator of these processes, yet dual maternal-neonatal methylation landscapes in PTB remain insufficiently characterized. Methods Genome-wide DNA methylation profiling was performed using long-read sequencing in matched maternal peripheral blood and neonatal cord blood from 15 PTB and 7 full-term QULSS2025 mother–infant pairs. Differentially methylated loci (DMLs) and regions (DMRs) were identified and evaluated by gene ontology and pathway enrichment analysis. Results We identified 25,336 DMLs and 1,151 DMRs across maternal and neonatal samples. In maternal blood, MED38, PSMB11, and WNT7B were hypermethylated, whereas EXTL3 and MMP9 were hypomethylated; in cord blood, ISG20, LMTK3, COL4A2, and TCAF2 were hypermethylated with EXTL3 and MMP9 consistently hypomethylated across tissues. Promoter-level alterations included hypermethylation of DKK3, CELF2, and IFI35, and hypomethylation of ALOX12 and CLBA1. These epigenetic shifts were enriched in developmental, immune, and neuroendocrine pathways, including the Wnt, MAPK, calcium, oxytocin, and neuroactive ligand–receptor signaling pathways. Comparative analysis revealed 120 shared DMLs (91 hypermethylated and 29 hypomethylated) and 14 shared DMRs mapped to genes such as PLD5, FBXO40, GMNC, HHIP, CLEC18B, and LHX1, indicating non-random chromosomal clustering. These shared regions were enriched in skeletal morphogenesis, axis patterning, and fibroblast growth factor signaling, suggesting convergence on core developmental regulatory pathways in PTB. Conclusion This first dual-tissue long-read methylation study in PTB reveals coordinated and tissue-specific epigenetic remodeling across the maternal–fetal interface. These shared signatures highlight potential biomarkers for risk stratification of PTB and may inform future early-intervention strategies. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx